Roofline analysis with Cray performance analysis tools (CrayPat) and roofline‐based performance projections for a future architecture. (25th September 2018) - Kwack, JaeHyuk; Arnold, Galen; Mendes, Celso; Bauer, Gregory H.
Summary: The roofline analysis model is a visually intuitive performance model used to understand hardware performance limitations as well as potential benefits of optimizations for science and engineering applications. Intel Advisor has provided a useful roofline analysis feature since its version 2017 update 2, but it is not widely compatible with other compilers and chip‐architectures. As an alternative, we have employed Cray Performance Analysis Tools (CrayPat) that are more flexible for multiple compilers and architectures. First, we present our procedure for measuring a reliable computational intensity for roofline analysis. We performed several numerical studies for validation via manually derived reference data as well as data from Intel Advisor. Second, we provide roofline analysis results on Blue Waters for several HPC benchmarks and sparse linear algebra libraries. In addition, we present an example of roofline‐based performance projection for a future system.